HUBUNGAN POLA AKTIFITAS DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS HALONG KABUPATEN BALANGAN - Sahmilni, Sahmilni; Basit , Mohammad; Latifah, Latifah; Tjomiadi, Cynthia Eka Fayuning (STIKES Suaka Insan, 2025)
Hypertension is a prevalent health issue among the elderly population and is often associated with low levels of physical activity. This condition can diminish quality of life and elevate the risk of further complications. This study aimed to analyze the relationship between physical activity patterns and the incidence of hypertension in the elderly. A quantitative study with a correlational design was conducted within the working area of the Halong Community Health Center, Balangan Regency. A total of 91 elderly respondents participated in this research, selected using a simple random sampling technique. Data were analyzed using the Spearman Rank correlation test to examine the relationship between variables. The results indicated that the majority of respondents had a good activity pattern (57.1%) and suffered from stage I hypertension (44.0%). Bivariate analysis confirmed a statistically significant negative correlation between activity patterns and the incidence of hypertension (p = 0.017). It was concluded that there is a significant relationship between activity patterns and the incidence of hypertension in the studied elderly population, wherein better activity levels are correlated with a lower incidence of hypertension.